Investigations on the WEDM of Friction Stir Processed Magnesium/Graphene-Boron Nitride Hybrid Surface Composite through the Entropy-COPRAS Approach. (17th October 2022) - Kavimani, V.; Gopal, P. M.; Sivamaran, V.; Anand Babu, K.
Abstract : In this research, friction stir processing (FSP) is utilized to develop the graphene-boron nitride-reinforced hybrid magnesium surface composite with varying volume percentages of reinforcements. A Taguchi-coupled Entropy-COPRAS approach is adopted to understand the influence of control factors of wire electrical discharge machining on the developed magnesium surface composite. An optimal combination of machining factors to attain maximum material removal rate (MRR) along with minimal kerf width and surface roughness is to be finalized. The Taguchi method is utilized for planning the experiments with three levels and four factors, namely, reinforcement volume %, pulse off time, wire feed rate, and pulse on time. ANOVA results show that pulse on time and reinforcement volume % act as the most significant factors for output responses. Using the Entropy-COPRAS approach, an optimal combination for output response was found for a maximum MRR of 16.20 mm 3 /min; minimal surface roughness of 3.86 μ m; and 0.29 μ m of kerf width.